2020
DOI: 10.1016/j.omtm.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ER Stress by an AAV5 BDD FVIII Construct Is Dependent on the Strength of the Hepatic-Specific Promoter

Abstract: Adeno-associated virus 5 (AAV5)-human factor VIII-SQ (hFVIII-SQ; valoctocogene roxaparvovec) is an AAV-mediated product under evaluation for treatment of severe hemophilia A, which contains a B-domain-deleted hFVIII (hFVIII-SQ) transgene and a hybrid liver-specific promotor (HLP). To increase FVIII-SQ expression and reduce the vector dose required, a stronger promoter may be considered. However, because FVIII-SQ is a protein known to be difficult to fold and secrete, this could potentially induce endoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
(85 reference statements)
2
20
1
Order By: Relevance
“… 30 , 31 Studies in mice have shown that hepatocytes expressing B-domain-deleted FVIII (from vectors incorporating a stronger hepatic-specific promoter than is used in valoctocogene roxaparvovec) may mount an unfolded protein response, potentially inducing ER stress. 32 34 To investigate the possibility of ER stress in our samples, fluorescence signals for GRP78 and FVIII protein colocalized in ER were quantified on a per-cell basis. Within individual samples, hepatocytes with detectable hFVIII-SQ protein staining in the ER did not have elevated expression of GRP78 compared to hepatocytes without hFVIII-SQ staining in the ER (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 30 , 31 Studies in mice have shown that hepatocytes expressing B-domain-deleted FVIII (from vectors incorporating a stronger hepatic-specific promoter than is used in valoctocogene roxaparvovec) may mount an unfolded protein response, potentially inducing ER stress. 32 34 To investigate the possibility of ER stress in our samples, fluorescence signals for GRP78 and FVIII protein colocalized in ER were quantified on a per-cell basis. Within individual samples, hepatocytes with detectable hFVIII-SQ protein staining in the ER did not have elevated expression of GRP78 compared to hepatocytes without hFVIII-SQ staining in the ER (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that simply increasing FVIII expression in transduced cells may not be sufficient to overcome the poor durability of HA gene therapy and may even induce potential unwanted off-target and toxic responses. This view is further supported by a recent publication, showing that the overexpression BDD-FVIII in murine hepatocytes from an AAV vector induces the UPR (61), which may be avoided by achieving therapy through limited expression in a high percentage of hepatocytes.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, we demonstrate a role of diet in particular when expressing a therapeutic protein in the liver that is prone to misfolding and ER stress. While AAV-FVIII gene transfer has not been found to cause the level of hepatocyte apoptosis and liver injury that may occur with DNA vectors, multiple studies have shown induction of ER stress markers in mice in response to AAV-FVIII (50, 59, 60), and liver injury (albeit of unknown origin) occurred in patients treated with high-dose AAV-FVIII (9, 10) We have now directly shown that expression of SQ-BDD in primary human hepatocytes induced ER stress in a dose-dependent manner (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the production of AAV vectors with genomes >4.7 kb is challenging because they frequently contain truncated genomes during viral packaging and are unsuitable for full-length FVIII cDNA (10.6 kb) or even B-domain deleted FVIII cDNA (4.35 kb) gene delivery [ 48 ]. A previous report also showed that some patients may generate neutralizing antibodies or endoplasmic reticulum stress, which influences the treatment effect of AAV-based gene delivery [ 27 ]. Therefore, lipid-coated nanoparticles, such as PEI and DPPC, have been developed as nonviral delivery systems to transport DNA or drugs into cells.…”
Section: Discussionmentioning
confidence: 99%
“…A first-in-human clinical trial of an AAV5- hFVIII -SQ vector for treating 15 adults with severe hemophilia A concluded that the therapy was beneficial and safe [ 26 ]. However, the foreign gene size is limited in the AAV vector, and some patients will generate neutralizing antibodies or endoplasmic reticulum stress to influence the treatment effect [ 27 ].…”
Section: Introductionmentioning
confidence: 99%